The Impact of Self-Service Bans in the Retail Gasoline Market - Johnson, Ronald N.; Romeo, Charles J. (The Review of Economics and Statistics, 2000)
In 1968, 23 states barred the self-service sale of gasoline. By 1992, close to 80% of all gasoline sales nationwide were marketed through self-service, and only New Jersey and Oregon continued to ban self-service sales. This paper examines the rise of self-service gasoline and its impact on price and the structure of the retail gasoline sector. Using predicted values for self-service sales for New Jersey and Oregon, the findings indicate that the bans in those two states have affected the retail market structure by slowing the penetration of convenience store tie-ins, and have resulted in retail margins that are approximately $0.03 to $0.05 per gallon higher. However, the bans have provided little protection to smaller outlets, which was a stated objective of their proponents.